Adoptive T-cell therapy with hexon-specific Th1 cells as a treatment of refractory adenovirus infection after HSCT - Feucht, Judith; Greil, Johann (Blood, 2015)
Hematopoietic stem cell transplantation (HSCT) has improved over the last few decades. However, viral infections are often refractory to pharmacologic treatment and require alternative treatment strategies such as immunotherapy. Adenovirus (AdV) is th predominant disease-causing pathogen in pediatric HSCT. In a clinical trial, we analyzed safety and efficacy of ex vivo adoptive T-cell transfer (ACT) with hexon-specific T cells, predominantly of the T-helper cell 1 (Th1) phenotype, in 30 patients with AdV disease or viremia. ACT was feasible with no acute toxicities or significant onset of graft-versus-host disease. ACT led to in vivo antiviral immunity for up to 6 months with viral control, resulting in complete clearance of viremia in 86% of patients with antigen-specific T-cell responses. After ACT and a follow-up of 6 months, overall survival was markedly increased in responders (mean, 122 days; 15 survivors) compared with nonresponders who all died shortly after ACT (mean, 24 days; no survivors). AdV-related mortality was 100% in nonresponders compared with 9.5% in responders (≥1 log reduction of DNA copies per milliliter after ACT). In summary, ex vivo ACT of AdV-specific Th1 cells was well tolerated and led to successful and sustained restoration of T-cell immunity correlated with virologic response and protection from virus-related mortality. This cellular immunotherapy is a short-term available and broadly applicable treatment. The study is registered at European Union Clinical Trials Register as 2005-001092-35.